Analisis dan Perancangan Sistem Informasi Penggajian Karyawan Berbasis Web pada CV. Sartika Brownies Oven Surabaya - Sartika, Yuni; Sunarto, M.J. Dewiyani; Mastan, Ignatius Adrian (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Cv .Sartika brownies oven surabaya formed since 2005 , having 12 people salesman and 10 workers in production line , which are engaged in production and marketing brownies oven in the area surabaya , sidoarjo and malang .At the moment , salary employee there is 12,5 % of the payments or per day .While production for employees their salary now rp 1.500.000 and to salary admin rp 3.000.000 .The company still a administration companies like data processing employees , presence data , data debt employees and data processing allowance manually file or record book is the basis for calculating employees payrool .The determination of salary workers in cv.sartika have 3 requirement that attendance of , the number of allowance , and the number of debt employees .The problem is the mounting paper and files disheveled so that it difficult to admin in pursuit of data before. Based on the above, the company wants to design wake of a salary information system .But , because both own company in detail did not know what is needed in this payroll information system , so in this research will be conducted analysis system needs and design a system that is expected to developed and help out the company and owner in doing effective salary .Keywords: PayrollÂ information systems, administration, analysis andÂ design,